Measurement Invariance of the Meaning in Life Questionnaire Across 17 Countries - Schutte, Lusilda (2023)
The Meaning in Life Questionnaire assesses presence of and search for meaning in life. Although the questionnaire has shown promising psychometric properties in samples from different countries, the scale’s measurement invariance across a large number of nations has yet to be assessed. This study is aimed at addressing this gap, providing insight into how meaning in life is constructed and experienced across countries and into the extent to which cross-country comparisons can be made. A total of 3867 adult participants from 17 countries, aged 30–60, balanced by gender, and with at least secondary education, completed the questionnaire as part of the Eudaimonic and Hedonic Happiness Investigation. Single sample confirmatory factor analysis, multigroup confirmatory factor analysis, and alignment optimization were applied to investigate the scale’s performance across the samples. Good psychometric properties and high levels of approximate measurement invariance emerged for the Presence subscale after removal of item 9, the only reverse-phrased item. Performance of the Search subscale varied more across samples, suggesting caution in interpreting related results supporting approximate measurement invariance. The conceptualization of presence of meaning operationalized in the corresponding subscale (without item 9) appears consistent across countries, whereas search for meaning seems to be less universally homogenous and requires further exploration. Moreover, the Meaning in Life Questionnaire does not reflect the conceptual distinction between “purpose” and “meaning” currently acknowledged by researchers. This issue should be further explored in studies addressing the scale’s performance across cultures.